The Role of Alcohol Intoxication on Sentencing by Judges and Laypersons: Findings From a Binational Experiment in Germany and France - Bègue, Laurent (International criminal justice review, 2023)
Existing studies do not provide consistent results regarding the role of alcohol intoxication on sentencing, and little is known about the specificity of sentencing by judges when compared to the general population. In this study, we experimentally investigated the influence of the level of alcohol intoxication on the sentence given to a defendant who had committed an act of physical aggression toward another person. A large sample of judges (N = 1,207) and a representative sample from the general population (N = 1,972) from both Germany and France were randomly assigned to a written depiction of an assault case in which the protagonist had either previously drunk no alcohol, or 0.50 L, or 1.5 L of beer. The respondents were then asked to assign a sentence to the defendant from a range of predefined options. Based on previous studies on sentencing among judges, we hypothesized that they would deliver harsher sentences than the participants from the general population contrary to the “myth of judicial leniency.” Moreover, following attribution theory, we hypothesized that alcohol consumption would decrease the severity of the sentence chosen by the participants from the general population. It was expected that the judges would not be influenced by alcohol information because in both France and Germany, alcohol is not considered to be an aggravating factor in crime according to national laws. The results showed that irrespective of the level of alcohol intoxication, the judges recommended harsher sentences than the participants from the general population and tended to rely on fewer sentence options. However, contrary to our expectations, in both countries, the protagonist’s level of intoxication did not influence sentencing severity.